Oracle real application clusters - Vallath, Murali (Digital Press, 2004)
Clustered configuration first hit the scene nearly 20 years ago when Digital Equipment Corporation (DEC) introduced the VaxCluster. Until now, the topic of Real Application Clusters (RAC) implementation had never been fully explored. For the first time, Murali Vallath dissects RAC mysteries in his book Oracle Real Application Clusters to enlighten and educate readers on the internals of RAC operations, cache fusion, fusion recovery processes and the fast reconfiguration of RAC. This book provides comprehensive coverage of the features, technology and principles of RAC that is part of the Oracle9i release of Oracle's RDBMS product. It is divided into three main parts: application/database design, development and maintenance life cycles. Compared to its predecessor OPS, the architecture behind RAC implementation have changed significantly. Vallath discusses Oracle9i features in a RAC implementation with respect to usage and design considerations, as well as those parameters that are and are not applicable. Areas covered include partitioning, indexes, tablespace management, transaction management, backup and recovery principles. Performance tuning with examples, troubleshooting and problem solving scenarios are covered in detail, as well as discussions on the migration process from a single instance database to RAC and migration from an OPS implementation to RAC. Oracle Real Application Clusters takes readers through a logical flow from RAC concepts to operations, covering each facet with a fine-tooth comb. Vallath's skilled writing style makes each chapter entertaining and informative as only a true RAC connoisseur can provide. New and experienced users of RAC, as well as those seeking to expand their knowledge of this dynamic technology, will find this book to be a necessity for both home and office reference libraries.